Identification of recalcitrant compounds in a pilot-scale AB system: An adsorption (A) stage followed by a biological (B) stage to treat municipal wastewater. (April 2016) - Trzcinski, Antoine Prandota; Ganda, Lily; Yan Ni, Annie Soh; Kunacheva, Chinagarn; Qing, Zhang Dong; Lin, Li Leonard; Tao, Guihe; Lee, Yingjie; Ng, Wun Jern
Highlights: 47% more methane was produced from the A-stage sludge. Both sludges contained aromatics, long chain alkanes, acids and esters. After AD, there was a radical shift in SMPs. After AD, the total number of detected compounds was lower. After AD, there was a higher proportion of aromatics. Abstract: This manuscript presents a comparison of the A-stage and B-stage sludges in terms of anaerobic biodegradability and low molecular weight compounds present in the supernatant using Gas Chromatography–Mass Spectrometry (GC–MS). The GC–MS analysis of A-stage and B-stage supernatants identified respectively 43 and 19 organic compounds consisting mainly of aromatics (27.9% and 21%), alcohols (25.6% and 15%) and acids (30.2% and 15%). The methane potential was found to be 349 ± 1 mL CH4 /g VS and 238 ± 12 mL CH4 /g VS, respectively. After anaerobic digestion of these sludges, a greater proportion of aromatics (42% and 58%) and a lower proportion of acids (10% and 10%) and alcohols (16% and 10%) was observed.